Buckling behaviour and natural frequency of zigzag and armchair single-walled carbon nanotubes - Rahmandoust, Moones (2012)
In this study, single-walled carbon nanotubes were generated in their perfect state as finite element models in the MSC.Marc software. The buckling behaviour and resonant frequency modes of the two limiting cases of carbon nanotubes, i.e. the armchair and zigzag models, were studied. The obtained results were compared with the classical analytical solutions related to a similar continuum structure of a hollow cylinder. The buckling behaviour of single-walled carbon nanotubes under cantilever boundary conditions proved to be almost identical to the prediction of the classical Euler equation. Furthermore, there was very good agreement between the analytical and finite element results of the studied single-walled carbon nanotubes; though the achieved value of the first mode of frequency, obtained from the finite element results, was more accurate than the higher modes.